Study on bridging moiety effect on asymmetric double D–Π–A dyes - Utt Eiamprasert (2019)
© 2018 Elsevier B.V. A series of four new asymmetric di-anchoring dyes is reported, containing identical π spacer, acceptor, phenothiazine (PTZ) and arylamine (ArnN) moieties in the donor part but different bridging moieties (L): N–C bond, C–C bond, phenylamine and triphenylamine. Spectral, electrochemical, and photovoltaic experiments and density functional theory calculations were performed to understand the bridging moiety influence on the performance of A–π–ArnN–L–PTZ–π–A dyes. Among these four dyes, the dye incorporating the triphenylamine bridging unit shows the best photovoltaic performance: an open-circuit voltage (Voc) of 0.72 V, a short-circuit photocurrent density (Jsc) of 11.57 mA cm−2, and a fill factor (FF) of 0.63, corresponding to an overall conversion efficiency of 5.21% under a simulated AM 1.5 G illumination condition. The results indicated that the presence of the biaryl torsion at the bridging position effectively improved the photovoltaic performance of the dye-sensitized solar cells.